Dialectica reconciliae: Mazamisa’s contribution to the historical development of New Testament Interpretation in South Africa - Hombana, Mphumezi (Verbum et ecclesia, 2024)
This article attempts to position Prof Mazamisa’s possible contribution to the historical development of New Testament interpretation in South Africa. This investigation is based mainly on his PhD dissertation project published in the Netherlands, Kampan University. This article attempts to navigate through New Testament interpretation in South Africa from the early 1970s until 1987, when Mazamisa attained his doctoral dissertation. This article argues that Mazamisa’s approach to reading the New Testament text can be considered a possible bridge between the so-called ‘white versus black hermeneutics’, to bring reconciliation in this long-standing debate in South African hermeneutics. This could happen through what Mazamisa called ‘Dialetica Reconcilea’.Intradisciplinary and/or interdisciplinary implicationsThis article has intradisciplinary implications within the fields of New Testament studies and South African hermeneutics, while also opening up opportunities for interdisciplinary exploration at the intersections of theology, sociology, philosophy, education, cultural studies, and conflict resolution. It suggests that Mazamisa’s approach may offer insights into resolving long-standing debates within South African hermeneutics.